THE QUALITY OF TEST IN THE TEXTBOOKS - Nirwanto, Rahmadi (LP2M IAIN Palangka Raya, 2013)
This article was aimed to discuss the quality of test in textbook, specifically addressing: 1) the type of test used, 2) the level of Blooms taxonomy and 3) the quality of tests which included (a) the objective test, and (b) the subjective test. The method used in this research was the incorporation of quantitative approach and qualitative approach. Textbook used in this study was âProgress A Contextual Approach to Learning English (An English Textbook for Senior High School)â. This textbook was based on Education Unit Level Curriculum/SBC (School Based Curriculum). This book was used on the high school level. The result of the study were as follows: 1) there were two types of test used in the textbook: objective and subjective tests, 2) there were two levels of Bloomâs taxonomy to measure the test: knowledge and comprehension, 3) as for the quality of test, (a) the objective test which were multiple choice items and true-false items were in category of good, whereas matching items was found in category of poor and (b) the subjective test which were Yes No Question, WH Question, and completion items included into category of poor.